Experimental Investigation of Gas Transmission Pipeline Blockage Detection Based on Dynamic Pressure Method - Kele Yan; Dianqiang Xu; Qiong Wang; Jiawei Chu; Shengjie Zhu; Jiafei Zhao (Energies, 2023)
The blockage of natural gas pipelines caused by solid deposits such as hydrates is one of the major safety risks to transmission pipeline systems. The key to effective blockage relief or removal is to determine the location and severity of the blockage. In recent years, the pressure pulse wave method has been considered as a practical detection method due to its fast response time, simplicity of operation, and extended detection distance. Nevertheless, the current implementation of this method in pipelines indicates that the accuracy in detecting blockages is very low. To improve the accuracy of the pressure wave blockage detection technique in our experiments, a series of experiments were carried out to detect and locate hydrate blockages in natural gas pipelines based on the pressure wave method using a separate pipeline system of 22 mm diameter and 106 m length. The experimental results show that the accuracy of the blockage location prediction based on the pressure pulse wave method is within 5%. Still, the blockage’s cross-sectional shape can significantly affect the intensity of the reflected wave, with a maximum prediction error of 35%.